Comparative antioxidant and anti-inflammatory activity of different extracts of centella asiatica (L.) urban and its active compounds, asiaticoside and madecassoside. - Nurlaily A,; Noor Baitee AR,; Musalmah M, (Penerbit UKM, 2012)
The potential of Centella asiatica (CA) as an antioxidant and anti-inflammatory agent has been well described. However the extraction method which gives the best yield is debatable. In this study, we evaluated three different methods of extractions and compared the extracts in terms of antioxidant, anti-inflammatory activities as well as the contents of its bioactive compounds, asiaticoside and madecassoside. Centella asiatica was extracted using ethanol, methanol and aqueous extraction methods. The extracts were then measured for their phenolic contents using Folin-Ciocalteu reagent. Asiaticoside and madecassoside were determined using HPLC. Antioxidant activity was measured using the 2,2-diphenyl-1-picrylhydrazyl (DHPP) and ferric reducing antioxidant power (FRAP) assays. Anti-inflammatory activities were determined by the ability of the extracts to inhibit the inflammatory pathway enzyme, COX-1 and COX-2 as well as their ability to protect fibroblasts against 12-O-tetradecanoylphorbol-13-acetate (TPA) -induced production of prostaglandin E2 (PGE2). Results showed that the level of phenolic constituents, asiaticoside and madecassoside were highest in the ethanol, followed by methanol and then aqueous extracts (17.76 g/100g, 15.52 g/100g, 13.16 g/100g for phenolics, 42.86 mg/g, 36.37 mg/g, 2.82 mg/g for asiaticoside and 18.66 mg/g, 15.87 mg/g, 3.75 mg/g for madecassoside respectively. All extracts showed considerable antioxidant activity compared to the positive controls. The extracts, asiaticosside and madecassoside inhibited both COX-1 and COX-2 and suppressed the TPA-induced production of PGE2. The ethanol and methanol extracts were stronger COX inhibitors and more potent suppressor of PGE2 formation than aqueous extract. Thus although the aqueous extract showed higher antioxidant potential, in terms of anti-inflammatory activities, the hydrophobic solvents, ethanol and methanol, proved to be the better extraction method for Centella asiatica.